Uranium in groundwaters from Botucatu-Piramboia aquifer, Brazil - Bonotto, Daniel Marcos [UNESP] (Wit Press/computational Mechanics Publications, 1999)
Groundwater from 60 pumped tubular wells of the Botucatu-Piramboia aquifer system located at the Parana sedimentary basin in Brazil were chemically analysed with the aim of evaluating if the mechanisms related to the migration of uranium can generate concentrations greater than the maximum permissible limit in drinking water, as defined by the Brazilian national standards.